Evaluation for Comorbidities Important in Psoriasis - Nichols, Emma Hitt (MD Conference Express, 2014)
Patients with psoriasis are at an increased risk of developing multiple comorbidities, including psoriatic arthritis (PsA), cardiovascular disease, diabetes mellitus, and cancer. This article discusses the practical aspects of diagnosing and managing patients, cardiometabolic risk assessment in patients with psoriasis, as well as systemic comorbidities with psoriasis.